Evaluation of whisker alignment and anisotropic mechanical properties of ZK60 alloy reinforced with SiCw during KOBO extrusion method. (December 2022) - Liu, Shoufa; Wang, Yinwei; Yarigarravesh, Mahdireza; Tayyebi, Moslem; Tayebi, Morteza
Abstract: In current study, microstructure and high-temperature mechanical properties of ZK60 magnesium alloy reinforced by SiC whiskers were investigated after casting, the KOBO extrusion and aging processes. For this purpose, ZK60/SiCw composite specimens were prepared by stir casting technique. In order to achieve a laminar structure and improve the strength, the samples were subjected to KOBO extrusion technique and precipitation hardening, resulting in improved strength and increased ductility. The former is due to grain refining and formation of precipitates in the microstructure, while the latter is attributed to grain refining and formation of laminar structure. To evaluate the strength of the specimens, tensile test was carried out at ambient and high temperatures. It was found that the alignment of whiskers and crystalline orientation during the KOBO extrusion process increased the anisotropic strength along with improvement of elastic modulus specially in the extrusion direction. Moreover, characterization results after the hot tensile test determined that with increasing the test temperature, yield stress, ultimate tensile strength (UTS), and elastic modulus declined nonlinearly. At last, fracture surfaces of the composite samples were investigated and it was confirmed that the applied load caused the fracture of the whiskers and, on the other side; cavity nucleation resulted in significant elongation in the specimens. Graphical abstract: Unlabelled Image